PENERAPAN STRATEGI BELAJAR MOOD, UNDERSTAND, RECALL, DIGEST, EXPAND, REVIEW (MURDER) DALAM MENINGKATKAN HASIL BELAJAR BIOLOGI KONSEP SISTEM EKSKRESI MANUSIA PADA KELAS XI IPA1 SMA NEGERI 1 KAIRATU - Roger Lopulalan; M Nur Matdoan (Program Studi Pendidikan Biologi FKIP Unpatti, 2016)
Background: One of the interesting and applicable learning strategies in the learning process is the MURDER learning strategy. Where this learning strategy aims to train and facilitate students in receiving and understanding the material provided. With the strategy of learning murder is expected the students get involved further in the process of teaching and learning effectively so that students are encouraged to understand every material in teaching teachers. Methods: Instruments used in this study are non-test instruments in the form of affective ratings sheets and psychomotor sheets and test instruments in the form of items used for initial and final tests. Data collection is done by literature, student learning result test, interview and observation. The data have been obtained in the form of scores analyzed in the form of product moment statistics to see the relationship between the results of learning results by using learning strategies MURDER. Result: Inferential statistic analysis showed that in table